2005
DOI: 10.1111/j.1745-4549.2004.23051.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Modified Atmosphere Packaged “Bartlett” Pears as Influenced by Time and Type of Storage

Abstract: Commercially mature “Bartlett” pears for this study were obtained from local commercial packing facilities. In the first year, pears were packed in modified atmosphere bags and placed in boxes or packed normally (control) with an individual paper wrap around each pear plus a polyethylene liner in the box. Boxed pears from both types of packaging were stored in regular atmosphere (RA) storage at 1C for 30 or 90 days. In the second year, pears were packed normally and stored in both RA or controlled atmosphere (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
1
4
2
Order By: Relevance
“…In this sense, this characteristic would allow the creation of a passive modified atmosphere system in a natural way that balanced oxygen and carbon dioxide inside these PET containers, favouring the growth of certain microorganisms. These results are in line with that reported by other authors [ 44 ] who concluded that the effect that modified atmospheres could have on microbial growth is largely unknown, as it depends largely on the barrier properties of the materials used. In general, Gram (−) bacteria are more sensitive to CO 2 than Gram (+) ones.…”
Section: Discussionsupporting
confidence: 93%
“…In this sense, this characteristic would allow the creation of a passive modified atmosphere system in a natural way that balanced oxygen and carbon dioxide inside these PET containers, favouring the growth of certain microorganisms. These results are in line with that reported by other authors [ 44 ] who concluded that the effect that modified atmospheres could have on microbial growth is largely unknown, as it depends largely on the barrier properties of the materials used. In general, Gram (−) bacteria are more sensitive to CO 2 than Gram (+) ones.…”
Section: Discussionsupporting
confidence: 93%
“…The results of other research conducted under normal MAP conditions (CO 2 concentration less than 20%) have shown retardation of discoloration in the fruits (Drake et al. 2004; Mahajan and Goswami 2004; Marrero and Kader 2006), while in this research, percentage of blemishing was not affected by gas concentration, with an exception of the MAP packages containing 85% CO 2 + 3% O 2 , and discoloration was enhanced slightly.…”
Section: Resultscontrasting
confidence: 63%
“…The results of other research conducted under normal MAP conditions (CO 2 concentration less than 20%) have shown retardation of discoloration in the fruits (Drake et al 2004;Mahajan and Goswami 2004;Marrero and Kader 2006), while in this research, percentage of blemishing was not affected by gas concentration, with an exception of the MAP packages containing 85% CO 2 + 3% O 2 , and discoloration was enhanced slightly. This was probably due to the very high concentration of CO 2 (Kader et al 1998 Ozkan et al (2004) that reduction of moisture content due to temperature increase is the reason for discoloration enhancement in dried apricots, but this is probably not the case here.…”
Section: Blemishing In Sayer Date Fruitscontrasting
confidence: 59%
“…The higher respiration rate observed in fruit packed with no-liner and macro-perforated liners may have contributed to the higher loss in fruit texture, compared to fruit packed in passively modified atmosphere by non-perforated liners. Drake et al [ 52 ] observed that ‘Bartlett’ pears at low temperatures of 1 °C packed in MAP liners retained more fruit firmness than pear packed under regular atmosphere. The authors reported that storing pears under controlled atmosphere retained fruit firmness throughout cold storage, irrespective of packaging treatment.…”
Section: Resultsmentioning
confidence: 99%